Alterations of the Brain Reward System in Antipsychotic Naïve Schizophrenia Patients - Nielsen, Mette Ødegaard; Rostrup, Egill; Wulff, Sanne; Bak, Nikolaj; Lublin, Henrik; Kapur, Shitij; Glenthøj, Birte (Biological psychiatry (1969), 2012)
Various schizophrenic symptoms are suggested to be linked to a dysfunction of the brain reward system. Several studies have found alterations in the reward processing in patients with schizophrenia; however, most previous findings might be confounded by medication effects. Thirty-one antipsychotic-naïve schizophrenia patients and 31 age- and gender-matched healthy control subjects were examined with functional magnetic resonance imaging while playing a variant of the monetary incentive delay task. The task variant made it possible to separate overall salience (defined as arousing events) into behavioral salience (events where a predicted reward requires performance) and valence anticipation (the anticipation of a monetarily significant outcome). Furthermore, the evaluation of monetary gain and loss was assessed. During reward anticipation, patients had a significant attenuation of the activation in ventral tegmentum, ventral striatum, and anterior cingulate cortex during presentation of salient cues. This signal attenuation in ventral striatum was correlated with the degree of positive symptoms. Signal attenuation was most pronounced for behavioral salience and nonsignificant for value anticipation. Furthermore, patients showed a changed activation pattern during outcome evaluation in right prefrontal cortex. Our results suggest that changes during reward anticipation in schizophrenia are present from the beginning of the disease. This supports a possible involvement of reward disturbances in the pathophysiology of schizophrenia. The most pronounced changes were seen in relation to overall salience. In ventral striatum these changes were associated with the degree of positive symptoms.